A giant landslide on the north flank of Tenerife, Canary Islands - Watts, A; Masson, D (1995)
Marine surveys show that, north of Tenerife, a giant landslide is exposed over an area of 5500 km2 of the seafloor, more than twice the surface area of the island. The landslide truncates an older ridge and valley topography that is associated with the shield building basalts on Tenerife. The ridge and valley topography is interpreted as the result of subaerial erosion. A young age for the landslide is supported by the 3.5-kHz echo sounder data which show that the landslide is draped by a thin (<10 m) layer of younger sediment. The landslide did not form, however, during a single catastrophic event but represents the amalgamation of a number of separate landslides. The giant landslide is associated with the late stages in the development of the most recent volcano on Tenerife, Las Canadas, which only began at about 1.8 Ma. -from Authors